2017
DOI: 10.1016/j.jaci.2016.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variation of serum periostin levels in adults with stable asthma

Abstract: Braithwaite have all received grants from Genentech. C. Holweg is an employee of Genentech, a member of the Roche group. J. Matthews is employed by Genentech, a member of the Roche group, and is a named inventor on a pending patent application assigned to his employer relating to subject matter in the manuscript. R. Beasley reports grants from Genentech during the conduct of the study and personal fees from the Health Research Council of New Zealand, GlaxoSmithKline, AstraZeneca, and Novartis and grants from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Another group looked at fluctuations in periostin levels in adults and found no evidence of fluctuation in serum levels over an 8-week period, suggesting levels in adults are stable. 70 Furthermore, the authors found no evidence of a seasonal effect on periostin levels. Together, these studies support the use of serum periostin as a biomarker for type 2-high asthma in adults and children.…”
Section: Biomarker Discovery In Asthmatic Patientsmentioning
confidence: 91%
“…Another group looked at fluctuations in periostin levels in adults and found no evidence of fluctuation in serum levels over an 8-week period, suggesting levels in adults are stable. 70 Furthermore, the authors found no evidence of a seasonal effect on periostin levels. Together, these studies support the use of serum periostin as a biomarker for type 2-high asthma in adults and children.…”
Section: Biomarker Discovery In Asthmatic Patientsmentioning
confidence: 91%
“…The concept that the presence of high periostin levels may identify patients who are likely to respond to monoclonal antibody treatment directed against type-2 inflammation 4 was confirmed by a randomised controlled trial (RCT) of lebrikizumab (anti-IL-13 therapy) in adults with moderate-to-severe asthma and uncontrolled symptoms despite ICS therapy 14 . The "periostin-high" patients (those with a periostin level ≥ 50 ng/ml, the median observed in the patient cohort being analysed) had a greater improvement in FEV 1 in the lebrikizumab treatment arm compared to placebo whereas the "periostin-low" patients did not (Fig.…”
Section: Predicting Responsiveness To Monoclonal Antibody Therapiesmentioning
confidence: 98%
“…1b) 12 . In studies of predominantly Caucasian adults with asthma using the Elecsys ® Periostin immunoassay the median (IQR) periostin levels were between 47.7 (40.2 to 56.3) ng/ml and 54 (46 to 62) ng/ml (Table 1) [13][14][15]17,38,43,44,49,[54][55][56][57] . This is similar to a predominant Caucasian non-asthma population in which the median (IQR) level of 50.1 (43.1 to 56.9) ng/ml has been derived 38 .…”
Section: Asthma Versus Non-asthmamentioning
confidence: 99%
See 2 more Smart Citations